Cross-Cultural Adaptation and Expert Opinion of Revised Trauma Quality of Life Questionnaire (RT-QoL): Malay Language Version - Wan Puteh, Sharifa Ezat; Ibrahim, Shamsinar; Zulkifli, Malina; Aizuddin, Azimatun Noor; Mohd Yusoff, Hanizah (Makara Journal of Health Research, 2025)
Background: This study examines the cross-cultural adaptation and expert validation of the Revised Trauma Quality of Life (RT-QOL) questionnaire, translating it from English to Malay. Methods: The study employed Beaton’s adaptation guidelines and Takasaki’s framework for expert opinions, involving 51 road traffic injury patients recruited from the Emergency and Trauma Department (ED) of a public hospital in Kedah, Malaysia, from March to June 2022. Participants were contacted via telephone 30 days after their hospital visit regarding their involvement in the study. Three independent experts, comprising academicians in healthcare and emergency department clinicians, reviewed and reconciled the RT-QOL Malay translation to ensure content validity and practical usability. Results: The Malay version exhibited satisfactory internal consistency, with reliability scores between 0.68 and 0.90, similar to those of the English version. The findings indicate that the questionnaire is appropriate for larger-scale studies, providing a useful instrument for assessing trauma-specific conditions in Malaysian contexts. Conclusion: This study represents the inaugural local examination of quality of life in road traffic injury patients utilizing the RT-QOL in Malay. This study establishes a basis for future research utilizing the RT-QOL Malay version to improve the comprehension and management of trauma-related quality of life concerns in the region.